Penerapan Kemanan Pangan Olahan di Kebabfactory - Nurindah, Putri; Charina, Anne (Universitas Galuh, 2026)
Micro, small, and medium enterprises (MSMEs) in the food sector play an important role in the national food system, but often face challenges in implementing product quality and safety standards. One strategy to enhance MSMEs' capacity to implement food safety is the launch of the “Safe Food Goes to Campus” (PAGC) program by the Indonesian Food and Drug Administration (BPOM), which involves students as mentors for food MSMEs in the implementation of Good Manufacturing Practices for Processed Foods (GMP-P). This study aims to evaluate the role of students in improving the quality of Kebabfactory products through training, production facility improvements, and documentation guidance. This study employs a qualitative approach with a case study design, utilizing data collection techniques such as in-depth interviews, field observations, and documentation. Data analysis was conducted using NVivo software to systematically map the findings. The results of the study indicate that student involvement has a positive impact on improving business operators' understanding of quality standards, the implementation of good production practices, and increased consumer confidence in the products. However, the study also identified challenges faced by business operators, namely the relatively short duration of the training, which prevented the material from being fully applied across all aspects of production.